Phase I Study of Nintedanib Incorporating Dynamic Contrast-Enhanced Magnetic Resonance Imaging in Patients With Advanced Solid Tumors. (20th March 2015) - Lee, Chooi Peng; Taylor, N. Jane; Attard, Gerhardt; Pacey, Simon; Nathan, Paul D.; Bono, Johann S.; Temple, Graham; Bell, Susan; Stefanic, Martin; Stopfer, Peter; Tang, Adrian; Koh, Dow-Mu; et al.
Abstract: Author Summary: Background: This open-label phase I dose-escalation study investigated the safety, efficacy, pharmacokinetics (PK), and dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) effects of the oral angiokinase inhibitor nintedanib in patients with advanced solid tumors. Methods: Nintedanib was administered once daily continuously, starting at 100 mg and later amended to allow evaluation of 250 mg b.i.d. The primary endpoint was maximum tolerated dose (MTD). DCE-MRI studies were performed at baseline and on days 2 and 28. Results: Fifty-one patients received nintedanib 100–450 mg once daily ( n = 40) or 250 mg b.i.d. ( n = 11). Asymptomatic reversible liver enzyme elevations (grade 3) were dose limiting in 2 of 5 patients at 450 mg once daily. At 250 mg b.i.d., 2 of 11 patients experienced dose-limiting toxicity (grade 3 liver enzyme elevation and gastrointestinal symptoms). Common toxicities included fatigue, diarrhea, nausea, vomiting, and abdominal pain (mainly grade ≤2). Among 45 patients, 22 (49%) achieved stable disease; 7 remained on treatment for >6 months. DCE-MRI of target lesions revealed effects in some patients at 200 and ≥400 mg once daily. Conclusion: Nintedanib is well tolerated by patients with advanced solid malignancies, with MTD defined as 250 mg b.i.d., and can induce changes in DCE-MRI. Disease stabilization >6 months was observed in 7 of 51 patients.